Phylogeny of the Paniceae (Poaceae: Panicoideae): integrating plastid DNA sequences and morphology into a new classification - Morrone, Osvaldo (2012)
Included in the PACMAD clade of the family Poaceae (Panicoideae, Arundinoideae, Chloridoideae, Micrairoideae, Aristidoideae, Danthonioideae), the tribe Paniceae s.l. is one of the largest tribes of the subfamily Panicoideae, with more than 2000 species. This tribe comprises a huge morphological, cytological and physiological diversity represented by different inflorescence types, several basic chromosome numbers, and at least four major photosynthetic pathways. The tribe Paniceae has been the subject of molecular studies that have confirmed its paraphyly: two major clades were recognized based on their basic chromosome numbers (x = 9, x = 10). The x = 10 Paniceae clade is sister to the Andropogoneae–Arundinelleae s.s. clade (x = 10), while the combined x = 10 clade is sister to the x = 9 clade that contains the remaining genera of Paniceae. As a result of a recent realignment within the tribe in terms of the phylogenetic position of minor and major Paniceae genera, a reanalysis of the whole sampling is performed and new underrepresented taxa are discussed. A total of 155 genera, currently considered within subfamily Panicoideae, are represented here by almost all genera of Paniceae s.l., representatives of Andropogoneae and Arundinelleae s.s., and the endemic and small tribe Steyermarkochloeae; we also included specimens of subfamily Micrairoideae, tribes Isachneae and Eriachneae. The sampling includes as outgroups 18 genera of the PACMAD clade (excluding Panicoideae) and four genera from the BEP clade (Bambusoideae, Ehrhartoideae, Pooideae), rooting with Bromus inermis. A matrix with 265 taxa based on the combined evidence from ndhF plastid sequences (2074 bp) and 57 morphological characters was subjected to parsimony analyses. Jackknife resampling was used to calculate group support. Most clades are characterized by morphological, cytological, anatomical, and⁄or physiological characters. Major tribal changes are based on the basic chromosome number; the pantropical x = 9 clade is here recognized as Paniceae s.s., while the American x = 10 Paniceae s.l. is restricted to the reinstated tribe Paspaleae. The optimization of the photosynthetic pathway for the Paspaleae–Andropogoneae– Arundinelleae s.s. clade, including the monotypic Reynaudia, shows a plesiomorphic C4 state while the ancestral state for Paniceae s.s. is ambiguous. If Reynaudia were not included or placed elsewhere, the ancestral photosynthetic pathway for both the Paspaleae– Andropogoneae–Arundinelleae s.s. clade and the Paniceae s.s. would be unambiguously C3. In order to explore character evolution further, the morphological characters were mapped onto one of the most parsimonious trees. A relationship between photosynthetic pathways and inflorescence morphology is suggested here for the first time. Based on the optimization of morphological characters and additional data, we propose names for almost all inner clades at the rank of subtribe with a few groups as incertae sedis. With this extensive sampling, we resolved the phylogenetic relationships and the assignation of synapomorphies, and improved the support in subtribe sorting; consequently a robust circumscription of the tribe Paniceae s.l. is proposed.